Implementasi Nilai-Nilai Pancasila dalam Kegiatan Kepramukaan di SMA Negeri 5 Kota Gorontalo - Pratiwi Ama; Sukarman Kamuli; Asmun Wantu (Journal on Education, 2024)
This research aims to discuss the implementation of Pancasila values in scouting activities at SMA Negeri 5 Gorontalo City. In research using qualitative methods with a descriptive approach, data is obtained through observation, documentation and direct interviews with informants in order to strengthen the data obtained by researchers. The results of research on the implementation of Pancasila values in scouting activities are very effective. This is indicated by the attitude of scout members who always prioritize unity, religion, independence, hard work, fairness, mutual cooperation, discipline, and in every impartial decision making, of course this is based on every scout member's practice of the contents of scout satya and scout dharma. Meanwhile, the factors that influence the implementation of Pancasila values can be seen from the supporting factors, namely parental support and the attitude of scout leaders who are always open to scout members, while the inhibiting factors are caused by the Covid-19 pandemic which has resulted in scout activities being ineffective because learning is being carried out. with online, on the other hand, there is a lack of student discipline so that many still arrive late at every activity or meeting, so there is a need for strengthening and evaluating scout members.